Overexpression of LINCR in the developing mouse lung epithelium inhibits distal differentiation and induces cystic changes. Issue 7 (18th June 2015) - Londhe, Vedang A.; Tomi, Tomoko; Nguyen, Tam T.; Lopez, Benjamin; Smith, Jeffrey B.
<x xml:space="preserve">Abstract</x> Background : Lung maturation can be disrupted through pro‐inflammatory processes including intra‐uterine amniotic infection, mechanical ventilation, or oxidative stress. Lincr, originally identified as a gene induced in the lung by lipopolysaccharide (LPS), is also expressed in the developing lung. The Lung‐inducible Neuralized‐related C3HC4 RING domain (LINCR) protein is structurally related to Drosophila Neuralized, a regulator of the developmentally important Notch signaling pathway. LINCR is expressed in alveolar epithelial type II cells in the mature lung, and its expression is markedly increased by LPS and inflammatory cytokines. To test the hypothesis that targeted overexpression of LINCR in lung epithelium would interfere with normal lung development, we generated double transgenic mice that conditionally overexpress LINCR in lung epithelium under the control of doxycycline. Results : Single transgenic controls and double transgenic mice not treated with doxycycline were unaffected, but double transgenic mice exposed to doxycycline starting at embryonic day 6 developed markedly hypoplastic lungs with decreased numbers of alveoli and large cysts lined with a proximalized and poorly differentiated epithelium expressing Hairy/Enhancer of Split 1, an effector of Notch signaling. The phenotype was similar to that caused by overexpression of activated Notch1 in lung epithelium. Conclusions : LINCR may exert its effects on distal lung development in this model through activation of the Notch signaling pathway. Developmental Dynamics 244:827–838, 2015. © 2015 Wiley Periodicals, Inc.